1943
DOI: 10.1021/ja01249a025
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction between Quinones and Metallic Enolates. XVII. Dibromo-p-xyloquinone and Sodiomalonic Ester1

Abstract: DlBROMO-p-XYLOQUINONE AND SODIOMALONIC ESTER 1739 xanthone, m. p. 249-250 °. Ullmann and Wagner10 report 243°.o-Phenoxy-p-hydroxybenzoic Acid.-Demethylation of o-phenoxy-p-methoxybenzoic acid with aluminum chloride in benzene gave 54% of the hydroxy acid which melted at 163-164°after vacuum sublimation and crystallization from water.Anal. Caled, for C13Hio04 : 0,67.84; H, 4.27. Found: C, 67.64; H, 4.54. p-Phenoxy-o-hydroxybenzoic Acid.-The acid mixture resulting from the oxidation of the 3-methoxy aldehydes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1945
1945
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The residue was triturated with light petroleum ether (30 mL). After cooling, a white precipitate of 2,5-dimethyl-1,4-hydroquinone (0.42 g, 83%) was obtained: , mp = 122−124 °C; TLC R f = 0.50 ( n -hexane/diethyl ether, v/v = 5:5); 1 H NMR (CD 3 OD) δ 2.10 (s, 6H, CH 3 ), 6.50 (s, 2H, Ar CH); 13 C NMR (MeOD) δ 15.90 (CH 3 ), 118.12 ( Ar CH), 123.33 ( Ar C), 148.94 ( Ar C−OH). Anal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The residue was triturated with light petroleum ether (30 mL). After cooling, a white precipitate of 2,5-dimethyl-1,4-hydroquinone (0.42 g, 83%) was obtained: , mp = 122−124 °C; TLC R f = 0.50 ( n -hexane/diethyl ether, v/v = 5:5); 1 H NMR (CD 3 OD) δ 2.10 (s, 6H, CH 3 ), 6.50 (s, 2H, Ar CH); 13 C NMR (MeOD) δ 15.90 (CH 3 ), 118.12 ( Ar CH), 123.33 ( Ar C), 148.94 ( Ar C−OH). Anal.…”
Section: Methodsmentioning
confidence: 99%
“…The residue was triturated with light petroleum ether (30 mL). After cooling, a white precipitate of 2,5-dimethyl-1,4-hydroquinone (0.42 g, 83%) was obtained: 28,29 6-Hydroxy-2,2,5,8-tetramethylchroman (6). Into a solution of 2,5-dimethyl-1,4-hydroquinone (see above, 1.50 g, 10.85 mmol) in formic acid (14.03 mL, 98-100%) and THF (3.74 mL) was added dropwise 2-methyl-3-buten-2-ol (10.81 mmol, 1.13 mL) in THF (0.93 mL) under stirring at 100 °C.…”
Section: Synthesis and Compound Characterization Of Modelmentioning
confidence: 99%
“…CHs CH CCOOC2H6 This reaction between completely methylated quiñones and sodium enolates appears to be a promising method for the synthesis of 6-hydroxy-5,7,8-trimethylcoumarins substituted in the 3-position by such groups as carbethoxyl, acyl, cyano, etc. Smith and coworkers (216,217,218,220) have exhaustively investigated this reaction with various brominated methylquinones and found that they may react with a metallic enolate to produce either a coumarin by reaction with a methyl group or a quinone malonic ester by direct replacement of a bromine atom.…”
Section: Azy /mentioning
confidence: 99%
“…p-Xyloquinone was prepared from p-xylenol (4,5) and reduced to the hydroquinone XI by the method of Smith and Johnson (6). The hydroquinone melted at 210-213.5°.…”
Section: Oh XImentioning
confidence: 99%